Problem of measuring thermal conductivity in heterogeneous rocks - Ibrahim, Yasir (2012)
Thermal conductivity is a critical component in the evaluation of source rocks and reservoir rocks in petroleum geoscience. However, rock heterogeneity provides a daunting task with regards to estimating thermal conductivity on such materials. Essentially, the main problem in thermal conductivity estimations measurements is to get a reliable representative estimate. Therefore, the objective of this study was to determine if it were feasible to determine a representative value for the thermal conductivity of a heterogeneous rock. The study was also carried out to determine the optimum number of readings and samples required to get a statistically viable estimation of the thermal conductivity for such rocks. The thermal conductivity of twelve granite block samples from Lata Kinjang, Perak, was estimated using the needle probe method at 40o C. Each face on the granite blocks (0.1 x 0.15 x 0.05m) were subdivided into parallel lines of 0.01m apart. The thermal conductivity was estimated along these lines. Statistical means for each face tended to be different within each block. The standard deviations differed as well, implying that the thermal conductivity estimations were anisotropic between faces and within the faces. The study showed that there were significant variations along each face, between different faces and different blocks. The mean thermal conductivity estimated for 9 samples was 2.37 Wm-1k-1 with standard deviation of 0.20 and standard mean of error 0.067. The confidence interval taken was 95% with lower and upper intervals values of 2.22 and 2.53 respectively. The comparison of means at the face level, sample specimen level and collectively all samples, showed that the means are significantly different. Therefore, in order to get a statistically reliable representative value, a minimum number of 3 lines per block face, 3 faces per sample, and 4 samples per rock type are required. Keywords- thermal conductivity, Heat flow, Granitic rocks.